Faktor-Faktor yang Mempengaruhi Konsumsi Tablet Tambah Darah Sebagai Upaya Mengatasi Anemia pada Remaja Putri - Rima Dwi Pinilih; Wijayanti, Wijayanti; Desy Widyastutik (STIKES Columbia Asia Medan, 2025)
Background: Anemia is a very serious danger because it can interfere with child development, cause decreased immunity, decline in academic ability, and reduce fitness and productivity. Anemia in pregnant women and adolescent girls is caused by various things, including less than optimal consumption of iron tablets, food intake, and the presence of comorbidities. Objective: This study aims to obtain information about the factors that cause the behavior of using iron tablets in adolescent girls at the Youth Posyandu in Semanggi Village, Surakarta City. This study aims to obtain an overview of the extent to which adolescent girls know information about consuming iron tablets, and what their attitudes are towards their use. Method: This study explores the factors that influence adolescent girls in using iron tablets at the Youth Posyandu in Semanggi Village, Surakarta City. The variables studied are the level of knowledge and attitudes. This type of study is an analytical survey with a cross-sectional approach. Data were collected through questionnaires given to adolescent girls who have experienced menstruation. The sampling technique used total sampling with a total of 25 respondents. Data analysis was carried out using the chi-square test to determine significant relationships. Research Results: There is a positive relationship between the level of knowledge (p-value = 0.028) and attitude (p-value = 0.035) with the consumption of iron tablets. Conclusion: Knowledge related to anemia and iron tablets as well as attitudes are factors that influence adolescent girls in consuming iron tablets. Implications: The results of this study indicate the need to continuously improve health education through counseling activities at the Youth Posyandu, schools, and social media. These efforts can strengthen understanding and form a positive attitude of adolescent girls towards the consumption of iron tablets.